Domestic Product Involvement and Consumer Willingness to Buy Domestic Products: Empirical Testing of a Cognitive Consistency Theory Framework - Prince, Melvin (Journal of International Consumer Marketing, 2020)
This study investigates biases affecting domestic products willingness to buy (WTB). An interdisciplinary perspective uses the cognitive consistency theory as the framework for the development of a new model. The model includes domestic product involvement (DPI). The impact on WTB is predicted by consumer ethnocentrism, and product judgment, driven by DPI are tested with survey data from an adult sample of 255 UK consumers. The study concludes with observations about the value of research findings for marketing practice. © 2020 Taylor & Francis Group, LLC.
7 citations (Crossref) [2023-10-31] WOS:000517943000001
Keywords: Cognitive consistency theory; consumer ethnocentrism; dept.mkt; domestic product involvement; peer-reviewed; product judgment; willingness to buy